Neutrinoless double- decay in an SU(3)LU(1)N model - Pleitez, V. [UNESP]; Tonasse, M. D. [UNESP] (American Physical Society (APS), 1993)
We consider a model for the electroweak interactions with the SU(3)LU(1)N gauge symmetry. We show that the conservation of the quantum number F=L+B forbids the appearance of massive neutrinos and the neutrinoless double- decay ()0. Explicit or/and spontaneous breaking of F implies that the neutrinos have an arbitrary mass. In addition the ()0 decay also has some channels that do not depend explicitly on the neutrino mass. © 1993 The American Physical Society.